Adaptive finite-time fuzzy command filtered controller design for uncertain robotic manipulators. (11th February 2019) - Deng, Yanping
In this article, an adaptive fuzzy control command filtered control approach, which is capable of achieving finite-time trajectory tracking control of uncertain robotic manipulators, is proposed by using the backstepping control technique. To obtain a finite-time estimation of a virtual control input and its first-order derivative, a second-order finite-time command filter is designed. Based on the backstepping control technique, an adaptive fuzzy controller that guarantees not only that the tracking errors tend to an arbitrary small region in finite time but also that all signals in the closed-loop system keep bounded is established. Finally, the effectiveness of the proposed method is demonstrated by simulation on a two-link robotic manipulator.